Do ethinylestradiol (EE2) and levonorgestrel (LNG) affect fish energy reserves? Insights from female guppies - Waani, Eunice Clarissa Chamberly; Hastuti, Susanti Pudji; Nugroho, Rully Adi (Department of Biology, Faculty of Sci and Tech, Universitas Islam Negeri Alauddin Makassar, 2026)
Contraceptive pills containing 17α-ethinylestradiol (EE2) and levonorgestrel (LNG) can contaminate aquatic environments and affect fish physiology. However, studies on the effects of EE2 and LNG on fish physiology in Indonesia remain limited. This study aimed to investigate the effects of combined EE2 + LNG and fish feed on the energy reserves, specifically lipid and protein content, in female guppies (Poecilia reticulata). Fish were reared for seven days with or without feeding in 4-l aquaria containing 1 l of water (pH = 7.6 ± 0.06, temperature = 24.6 ± 2.08 ℃, BOD = 5.8 ± 0.76 mg l-1). Each aquarium contained five female fish (2–2.5 cm in length). Five EE2 + LNG concentrations were tested: 0 + 0, 3 + 15, 30 + 150, 300 + 1500, and 3000 + 15000 ng l-1, with three replicates. Lipid and protein contents were estimated gravimetrically and expressed in Joules (J). Data were analyzed using two-way ANOVA with EE2 + LNG concentration and feeding as factors, followed by Tukey’s post hoc test. Results showed no significant interaction or single factor effect of EE2 + LNG concentration and feeding on dry weight, lipid, or protein contents. Dry weight, lipid, and protein ranged from 17.8–118.0 mg, 0.01–0.49 J, and 0.29–1.94 J, respectively. Thus, exposure to EE2 + LNG did not affect the energy reserves of female guppies. This indicates that short-term exposure to EE2 and LNG at concentrations relevant to the environment does not lead to immediate disruption of energy metabolism in fish, and it also offers reference information for environmental surveillance and toxicological risk evaluation of endocrine-disrupting pharmaceuticals in water systems.